FACTORS ASSOCIATED WITH RECURRENT STROKE AT DR. M. HATTA BRAIN HOSPITAL, BUKITTINGGI, 2024 - Suci Dwi Meishindy; Bambang Susanto; Tri Makmur; Wan Muhammad Ismail (Poltekkes Kemenkes Bengkulu, 2025)
Stroke is a cerebrovascular disease that causes disability and death. Recurrent stroke occurs after the first stroke, due to the patient's lack of self-control and low level of awareness of stroke risk factors. Based on the 2023 Indonesian Health Survey (IHS), the prevalence of stroke in Indonesia is 8.3% cases per mile of population. Low knowledge, understanding, and awareness of risk factors for stroke are problems that arise in stroke services. Objective: To determine the factors associated with the incidence of recurrent stroke in stroke patients at Rumah Sakit Otak Dr. Drs. M. Hatta Bukittinggi. Methods: Using Analytic-Descriptive, purposive sampling technique totaling 99 people. Hypothesis analysis test using Chi-square test. Results: Based on age 47-52 as many as 20 people (27%), 45 men (60.8%), 51 people (68.9%), and have a family history of 48 people (64.9%). There is a significant relationship between recurrent stroke and age p-value= 0,001, gender p-value =0,031, ethnicity p-value= 0,044, family history p-value= 0,029, physical activity p-value= 0,000, smoking p-value= 0,000, diet p-value= 0,000, and control compliance p-value= 0,000 at Dr. Drs. M. Hatta Bukittinggi Brain Hospital. Conclusion: There is a significant relationship between age, gender, ethnicity, family history, physical activity, smoking, diet and control compliance with recurrent stroke.